Staphylococcus pseudintermedius and Staphylococcus schleiferi Subspecies coagulans from Canine Pyoderma Cases in Grenada, West Indies, and Their Susceptibility to Beta-Lactam Drugs - Harry Hariharan; Kathryn Gibson; Ross Peterson; Matthew Frankie; Vanessa Matthew; Joshua Daniels; Nancy A. Martin; Linton Andrews; Tara Paterson; Ravindra N. Sharma (Veterinary Medicine International)
Over a 2-year period 66 cases of canine pyoderma in Grenada, West Indies, were examined by aerobic culture in order to ascertain the bacteria involved and their antimicrobial resistance patterns. Of the 116 total bacterial isolates obtained, the majority belonged to Gram-positive species, and the most common organism identified through biochemical and molecular methods was Staphylococcus pseudintermedius. Additionally, identification of a Staphylococcus schleiferi subspecies coagulans isolate was confirmed by molecular methods. All isolates of staphylococci were susceptible to beta-lactam drugs: amoxicillin-clavulanic acid, cefovecin, cefoxitin, cefpodoxime, and cephalothin. They were also susceptible to chloramphenicol and enrofloxacin. Resistance was highest to tetracycline. Methicillin resistance was not detected in any isolate of S. pseudintermedius or in S. schleiferi. Among the Gram-negative bacteria, the most common species was Klebsiella pneumoniae, followed by Acinetobacter baumannii/calcoaceticus. The only drug to which all Gram-negative isolates were susceptible was enrofloxacin. This report is the first to confirm the presence of S. pseudintermedius and S. schleiferi subspecies coagulans, in dogs with pyoderma in Grenada, and the susceptibility of staphylococcal isolates to the majority of beta-lactam drugs used in veterinary practice.